2008
DOI: 10.1111/j.1574-6941.2008.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of phytotoxic compounds from torrefied grass fibres by plant-beneficial microorganisms

Abstract: We aimed to select microorganisms colonizing torrefied grass fibres (TGF) and simultaneously reducing the phytotoxicity which appeared after heat treatment of the fibres. Eighty-eight bacterial strains and one fungus, previously isolated from a sequential enrichment experiment on torrefied fibres and extracts, were tested separately for their capacity to decrease phytotoxicity. Eleven of the bacterial strains and the fungus significantly reduced phytotoxicity. These organisms were checked for their ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Th e GC-MS analysis showing the presence of phenolic compounds provides evidence that the high-VM charcoal contained readily available C sources for soil microorganisms. Th ere is ample evidence that both fungi and bacteria utilize phenolic compounds as a sole source of C (Saravanan et al, 2008;Stoilova et al, 2006;Trifonova et al, 2008). Th e results from our incubation studies (Exp.…”
Section: Treatment N P K Ca Mgmentioning
confidence: 81%
See 1 more Smart Citation
“…Th e GC-MS analysis showing the presence of phenolic compounds provides evidence that the high-VM charcoal contained readily available C sources for soil microorganisms. Th ere is ample evidence that both fungi and bacteria utilize phenolic compounds as a sole source of C (Saravanan et al, 2008;Stoilova et al, 2006;Trifonova et al, 2008). Th e results from our incubation studies (Exp.…”
Section: Treatment N P K Ca Mgmentioning
confidence: 81%
“…6a) contained a range of compounds including butyrolactone, phenol, cresol, mequinol, ethyl phenol, p-ethyl guaiacol, and syringol (Bocchini et al, 1997). Phenol is known to be phytotoxic (Wang et al, 2002), but both phenol and cresol are utilized as a C source by soil microorganisms (Saravanan et al, 2008;Trifonova et al, 2008). Th e chromatogram for the low-VM charcoal (Fig.…”
Section: Experiments 5: Effect Of Charcoal Volatile Matter Content Onmentioning
confidence: 98%
“…The majority of them have been isolated using classical enrichment on furfural as a carbon source (25,46,49). However, most of these isolated microorganisms are aerobic Gram-negative bacteria, with only three fungi reported as furfural degraders (23,39,51). Rosche et al (35) found 14 filamentous fungi that could biotransform benzaldehyde.…”
Section: Discussionmentioning
confidence: 97%
“…Hundreds of organic compounds with phytotoxic activity have been extracted from plant tissues, purified and identified (e.g. Rice, 1984;Rizvi & Rizvi, 1992;Reigosa et al, 2006), but the link between these single chemicals and the inhibitory effect of plant detritus has only been demonstrated in a limited number of cases (An et al, 2001;Trifonova et al, 2008). Recent studies have reported that plant litter is composed of a milieu of thousands of unique molecules that change during decomposition (Wallenstein et al, 2010).…”
Section: New Phytologistmentioning
confidence: 99%